ANTINUTRIENTS IN HERBAL PRODUCTS: AN ASSESSMENT OF NITRATE, PHYTATE, OXALATE, AND CYANIDE IN COMMONLY CONSUMED HERBAL SNUFFS IN SOKOTO, NIGERIA - Imam, Aminu Umar; Sarkingobir, Yusuf; Dikko, Malami; Shagari, Kasimu Abubakar; Sulaiman, Bello (Universitas Nahdlatul Ulama Surabaya, 2023)
Background: Herbs are major players in present day therapy, especially by the locals. However, there are some secondary metabolites present in them that can act as antinutrients when consumed by humans. Thus, it is important to monitor the levels of antinutreints in herbal snuff to save the public, especially in Sokoto (a state battling with challenges of nutrients deficiency and malnutrition). Objective: The objective of this work was to measure levels of cyanide, nitrate, phytate, and oxalate, in herbal snuff in Sokoto, Nigeria. Methods: Snuffs were brought from Sokoto market and subjected to antinutritional analysis according to standard methods and using reagents/materials of analytical grade. Result: The amount of nitrate present in three herbal snuff brands sold in Sokoto, Nigeria show that, nitrate ranges from 18.81 ± 0.9 mg/100g (found in Hajiya Safiya snuff brand) to 21. 82 ± 0.08 mg/100g (found in Hajiya Aisha snuff brand). The concentrations of phytate in 3 brands of herbal snuffs revealed, the highest value (91.164 ± 0.001 mg/100g) was recorded in Hajiya Aisha, and the lowest (4.05 ± 0.04 mg/100g) was observed in Dr Lambo herbal brand. The concentrations of oxalate show that, the highest level (0.0787 ± 0.059 mg/100g) was found in Dr lambo, and lowest (0.0055 ± 0.0001 mg/100g) observed in Hajiya Aisha snuff. Then, levels of cyanide in herbal snuff show, the highest value (25.68 ± 1.45 mg/ 100g) was recorded in Dr Lambo snuff brand, and the lowest level of cyanide was recorded in Hajiya Safiya (19.32 ± 1.04 mg/ 100g). Conclusion: The snuffs contain the assessed antinutrients at levels that are not likely to pose risk.